The Community Health Advocacy Initiative: A Longitudinal Experiential Curriculum in Community Engagement for Preclerkship Medical Students - Emma Anselin; Dakota Chisholm; Karen Sheehan; Ashti Doobay-Persaud (Association of American Medical Colleges, 2024)
Introduction Community partnership is a key strategy for addressing the social determinants of health and achieving health equity. There are few examples of curricula for undergraduate medical education that teach all, rather than self-selected, medical students to collaborate with community members to improve health. We describe the design and implementation of the Community Health Advocacy Initiative (CHAI) curriculum, a new yearlong educational program for medical students at Northwestern University's Feinberg School of Medicine. Methods CHAI aimed to fill the curricular gap in social determinants of health education by providing medical students with the knowledge and skills to improve the health of patients through collaborations with community partners. This longitudinal curriculum included structured faculty mentorship and an applied community experience. Results The CHAI curriculum was delivered to 164 second-year medical students in academic year 2021-2022. Faculty mentors rated most students as meeting expectations for application of community partnership principles and demonstration of professionalism. Qualitative analysis of faculty mentor comments demonstrated that medical students exhibited positive outcomes in engaging with community organizations, overcoming barriers, developing feasible and impactful goals, and advancing their own knowledge and skills. Discussion Implementing a community health curriculum for all medical students is feasible and represents an important model for teaching about the importance of community partnerships in addressing the social determinants of health.